METHODS OF TEACHING THE SUBJECT OF TECHNICAL MECHANICS IN DIRECTION OF TECHNOLOGICAL EDUCATION (Scientific journal of the Fergana State University, 2023)
This article presents opinions and considerations on the methodology of teaching the subject of Technical Mechanics in the field of technological education. Today, learning through the use of technology in education and teaching activities increases the effectiveness of the lesson. Very effectively helps to develop the imagination of students using new techniques. To date, the organization of high-quality education in technology lessons in secondary schools, the use of modern teaching methods, the formation of students' creative abilities are among the most pressing issues. As you know, the science of technology includes the topics of processing various materials, studying their specific properties. In this article, one of the most interesting topics about the methodology of teaching the discipline “Technical Mechanics" is widely covered.